Machine learning based data processing and latency reduction in the internet of things for agriculture - Rahman, Sajeed Ur; Dip, Leonard Michael Gomes; Shuddho, Manan Moin; Maheen, Kishwar (BRAC University, 2019)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2018.